Religiusitas dan Love Of Money : Dapatkah Mengurangi Kecenderungan Kecurangan - Koerul Rahmawadin; Umaimah Umaimah (Universitas Muhammadiyah Gresik, 2022)
This study aims to examine the differences in the tendency of cheating at high & low levels of religiosity and high & low levels of love of money. The theory of planned behavior is applied in this study using a laboratory experimental approach. The test used is a comparative analysis of the average independent sample t test. The sample used as the experimental subject was 104 students of the accounting study program at the University of Muhammadiyah Gresik. The results showed that there was a difference in the tendency of cheating between high & low levels of religiosity and there was no difference in the tendency of cheating between high and low levels of love of money.